Orthodontics as risk factor for temporomandibular disorders: A systematic review - Machado, Eduardo (2010)
Introduction: The interrelationship between orthodontics and temporomandibular disorders (TMD) has attracted an increasing interest in dentistry in the last years, becoming subject of discussion and controversy. In a recent past, occlusion was considered the main etiological factor of TMD and orthodontic treatment a primary therapeutical measure for a physiological reestablishment of the stomatognathic system. Thus, the role of orthodontics in the prevention, development and treatment of TMD started to be investigated. With the accomplishment of scientific studies with more rigorous and precise methodology, the relationship between orthodontic treatment and TMD could be evaluated and questioned in a context based on scientific evidences. Objective: This study, through a systematic literature review had the purpose of analyzing the interrelationship between orthodontics and TMD, verifying if the orthodontic treatment is a contributing factor for TMD development. Methods: Survey in research bases MEDLINE, Cochrane, EMBASE, Pubmed, Lilacs and BBO, between the years of 1966 and 2009, with focus in randomized clinical trials, longitudinal prospective nonrandomized studies, systematic reviews and meta-analysis. Results: After application of the inclusion criteria 18 articles were used, 12 of which were longitudinal prospective non-randomized studies, four systematic reviews, one randomized clinical trial and one meta-analysis, which evaluated the relationship between orthodontic treatment and TMD. Conclusions: According to the literature, the data concludes that orthodontic treatment cannot be considered a contributing factor for the development of temporomandibular disorders.